The meaningfulness of work: Employment and agency in Berlin - Weiss, H. (Anthropological Quarterly, 2025)
Drawing on my fieldwork on the work lives of professionals and jobseekers in Berlin, I identify a tension between a promulgated and widely shared ideal of employment as free, empowering, and meaningful, and an equally widely shared awareness of the circumstances that enable and limit one’s employment possibilities. This apparent contradiction is resolved by a rescaling. Specifically, in a reality circumscribed by the dynamic of accumulation, resources are afforded, primarily in and through employment, which allow those who can procure and mobilize them to experience, on a diminutive scale, what they are denied writ large: a sphere of agency through which to carve out a socially validated meaning. I describe how this state-regulated and supported rescaling shapes the ways in which men and women in Berlin relate to their current and ideal employment